2012
DOI: 10.1016/j.cmet.2012.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Zfp423 Expression Identifies Committed Preadipocytes and Localizes to Adipose Endothelial and Perivascular Cells

Abstract: Summary Progress has been made in elucidating the cell surface phenotype of primary adipose progenitors; however, specific functional markers and distinct molecular signatures of fat depot-specific preadipocytes have remained elusive. In this study, we label committed murine adipose progenitors through expression of GFP from the genetic locus for Zfp423, a gene controlling preadipocyte determination. Selection of GFP-expressing fibroblasts from either subcutaneous or visceral adipose-derived stromal vascular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
296
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 368 publications
(314 citation statements)
references
References 66 publications
(82 reference statements)
16
296
1
1
Order By: Relevance
“…Despite contrasting findings from different laboratories (60) our data, including lineage-tracing studies, seem to indicate that endothelial cells of adipose tissue capillaries are able to turn into pericytes and then into either white and brown adipocytes (61,62,63,64,65,66). Such unique origin could support their ability to undergo multiple changes before achievement of the adult phenotype.…”
Section: European Journal Of Endocrinologymentioning
confidence: 76%
“…Despite contrasting findings from different laboratories (60) our data, including lineage-tracing studies, seem to indicate that endothelial cells of adipose tissue capillaries are able to turn into pericytes and then into either white and brown adipocytes (61,62,63,64,65,66). Such unique origin could support their ability to undergo multiple changes before achievement of the adult phenotype.…”
Section: European Journal Of Endocrinologymentioning
confidence: 76%
“…Isolation of adipose SV fraction and differentiation of primary adipocytes was done as described previously (50). Oil red O staining was performed as described previously (51).…”
Section: Methodsmentioning
confidence: 99%
“…Using lineage tracing, Zfp423 has recently been identified as a factor playing a key role in the early commitment of both brown and white fat. Zpf423 is easily detected in both BAT and WAT preadipocyte depots in the adipose vasculature, coinciding with a subset of pericytes (Gupta et al 2012), suggesting once again a possible endothelial origin of fat. In an independent study, WAT precursors in adipose vasculature were also identified by Tang et al (2008).…”
Section: Bat Precursors In Adult Mice: Endothelial and Other Originsmentioning
confidence: 99%